The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1179/1607845415y.0000000049
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of hematopoietic stem cells mobilization in patients with multiple sclerosis

Abstract: Mobilization using CY and/or G-CSF resulted in effective mobilization in all MS patients. This procedure was found to be safe. No fatal outcome has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The NHF database is good for tracking the drug or procedure used but does not contain data on the stage or type of the disease, the EDSS scores, or MRI results, However, partial data of study population show median EDSS 6.5 prior to AHSCT and median EDSS 5.75 12 months after AHSCT. 17 Moreover, the suboptimal access to the drugs might also have an impact on the transplanted population, which seems to be younger than typical patients with "aggressive" forms of MS. 18 Patients with MS in Poland are qualified for AHSCT according to the European Group for Blood and Marrow Transplantation 2012 guidelines, which allow to qualify different patients with different forms of aggressive MS. 16 The database does not provide information on how intensive was immunoablation before AHSCT and which transplantation protocol was used. This impacts the cost of the procedure for the transplantation center and the long-term results of the AHSCT.…”
Section: Discussionmentioning
confidence: 99%
“…The NHF database is good for tracking the drug or procedure used but does not contain data on the stage or type of the disease, the EDSS scores, or MRI results, However, partial data of study population show median EDSS 6.5 prior to AHSCT and median EDSS 5.75 12 months after AHSCT. 17 Moreover, the suboptimal access to the drugs might also have an impact on the transplanted population, which seems to be younger than typical patients with "aggressive" forms of MS. 18 Patients with MS in Poland are qualified for AHSCT according to the European Group for Blood and Marrow Transplantation 2012 guidelines, which allow to qualify different patients with different forms of aggressive MS. 16 The database does not provide information on how intensive was immunoablation before AHSCT and which transplantation protocol was used. This impacts the cost of the procedure for the transplantation center and the long-term results of the AHSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In one study it was reported that HSCs expand regulatory cells and deplete IL-17 T-cells in MS [ 374 ]. Granulocyte colony-stimulating factor and cyclophosphamide resulted in an efficient HSC mobilization in MS patients [ 375 ]. In patients with relapsing-remitting MS, HSCs transplantation resulted in improvement in neurological disability [ 376 ].…”
Section: Polyphenols Utilizing Stem Cells Against Neurodegeneratiomentioning
confidence: 99%
“…This opens the possibility to apply AHSCT for any patient with any severe autoimmune disease -the only requirement is combined qualification by a rheumatologist or neurologist and hematologist. The transplantation centers in Katowice and Warsaw have already transplanted patients with multiple sclerosis, systemic sclerosis and type 1 diabetes [6][7][8]. There are also other centers that are willing to accept patients.…”
mentioning
confidence: 99%